Evaluating the Effects of Sonneratia alba Leaf in Feed on Growth Performance and Clinical Manifestations in Milkfish (Chanos chanos) Exposed to Vibrio harveyi - Linayati - Linayati; Tri Yusufi Mardiana; Maghfiroh Maghfiroh; Wildan Nurussalam; Syifania Hanifah Samara; Nguyen Duc Quynh Anh; Candra Adi Purnama (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2026)
Milkfish (Chanos chanos) cultivation faces challenges related to high feed costs and disease outbreaks caused by Vibrio bacteria. The use of natural ingredients containing bioactive compounds, such as Sonneratia alba mangrove leaves, as feed additives may serve as an effective solution. This study aimed to determine the effect of adding Pidada (S. alba) leaf extract at different doses to feed on growth performance and survival rates after infection with Vibrio harveyi. The experiment used a Completely Randomized Design (CRD) consisting of four treatments and three replications. The treatments included: A (control, artificial feed without extract), B (75 ppm per 500 g feed), C (125 ppm per 500 g feed), and D (170 ppm per 500 g feed). Treatment B produced the best biomass gain of 8.4 g, the best feed conversion ratio (FCR) of 1.16, and a feeding efficiency of 86.52 percent. The addition of S. alba leaf extract significantly improved growth and survival of milkfish infected with V. harveyi, with treatments B, C, and D maintaining a 100 percent survival rate after infection. Treatment A showed the lowest growth and survival, indicating that S. alba leaf extract positively supports fish health and enhances milkfish cultivation outcomes